Synthesis and Characterization of Transition Metal Complexes of Schiff Bases Derived from 3-Formyl Chromone - Devi, Jai; Yadav, Manju (Asian Journal of Chemistry, 2016)
A series of Co(II), Ni(II), Cu(II) and Zn(II) complexes derived from bidentate Schiff bases obtained by condensation of 3-formyl chromone with 5-chloro-2-phenoxy-phenylamine and 2-phenoxy-phenylamine to form 3-[(5-chloro-2-phenoxy-phenylimino)methyl]-chromen-4-one (L1) and 3-[(2-phenoxy-phenylimino)methyl]-chromen-4-one (L2) have been synthesized and characterized by molar conductance, magnetic moment, thermal studies and spectroscopic techniques (FTIR, UV-visible, 1H NMR, 13C NMR) having general formula M(L1-2)2·2H2O.